Demand for eggs attributes in Malaysia: evidence from conjoint survey - Abdul Hadi, Ahmad Hanis Izani; Shamsudin, Mad Nasir; Selamat, Jinap; Radam, Alias (2012)

(untitled)
There has been a clear increase in Malaysian per capita income in the last few decades. From economics point of view, it is expected that better-off consumers will move to better quality of food attributes such as freshness, food safety, quality and healthfulness in their food intake. This study aimed to investigate the demand for eggs attributes by Malaysian consumers. The study considers the conjoint analysis technique as a method for acquiring insights into preferences for eggs product. The technique was applied to establish the trade-offs that Malaysian consumers make between size, colour, size of packaging, functional attribute and price in the purchasing of eggs for 202 respondents. Least squares regression was utilized to estimate the relative importance of attributes for eggs. The results revealed that the ideal characteristic of egg was one with large size (grade A), omega eggs, brown, and ten per packs. Based on our calculation, we also found that consumers were also willing to pay for the demanded eggs attributes. The results found may encourage producers or marketers to adjust their marketing efforts to consider the important eggs attributes demanded by Malaysian consumers.